The Evolution of Quality of Life After Subthalamic Stimulation for Parkinson's Disease: A Meta‐Analysis - Büttner, Charlotte (Mov Disord Clin Pract, 2019)
BACKGROUND: Several studies examined the influence of subthalamic nucleus–deep brain stimulation (STN‐DBS) on quality of life (QoL) in patients with Parkinson's disease (PD). However, it is unclear whether this effect differs between age groups and disease durations and whether it stays consistent over time. OBJECTIVES: We assessed the influence of stimulation duration, disease duration, and age at surgery on QoL after STN‐DBS. METHODS: We systematically searched for studies reporting the results of the Parkinson's Disease Questionnaire 39 or 8. Studies were included if they investigated the time passed since STN‐DBS or if their study cohort fell into the range of one of the following age groups: younger than 60 years or between 60 and 70 years. For each condition, a standardized mean difference meta‐analysis was performed. Furthermore, all studies were categorized into short or long disease duration at surgery using a median split. RESULTS: A total of 23 studies reporting the cumulative outcome of 76 to 802 PD patients were included in this analysis. The results demonstrate a substantial improvement of QoL after DBS that remains stable over 36 months. QoL falls to preoperative scores 60 months after surgery. However, only 3 studies could be included in this analysis. Both younger and older PD patients profit in QoL from STN‐DBS, independent of the disease duration. CONCLUSIONS: The results of this analysis show an impressive improvement in QoL after STN‐DBS, with a loss of QoL 60 months after DBS surgery. This highlights the need to explore the factors influencing QoL after STN‐DBS to prevent or delay a decline in QoL.